Trends in Endoscopic and Microscopic Transsphenoidal Surgery: A Survey of the International Society of Pituitary Surgeons Between 2010 and 2020. (16th November 2020) - Khalafallah, Adham M; Liang, Angela; Jimenez, Adrian; Rowan, Nicholas; Oyesiku, Nelson M; Mamelak, Adam N; Mukherjee, Debraj
Abstract: INTRODUCTION: Eliciting trends in practice patterns for transsphenoidal surgery is important for identifying areas of improvement. METHODS: Web-based surveys were sent to the International Society of Pituitary Surgeons (ISPS) via a membership listserv in 2010 and 2020. These surveys collected information on demographics, surgical approach, perceived advantages and disadvantages, and recommendations for improvements. Statistical analyses were conducted using the Mann-Whitney U test for continuous variables and Fisher's exact test for categorical variables. RESULTS: There were 51 respondents in 2010 and 82 respondents in 2020. The majority were full-time academic surgeons from the United States or Europe. Preference for a purely endoscopic technique increased from 43% in 2010 to 87% in 2020. Preference for routinely working with an otolaryngologist or second neurosurgeon increased from 35% to 51%. Most surgeons (74%) reported that they were more likely to achieve a greater extent of resection with the endoscope, though 51% noted increased operating time. The most commonly rated advantage (34%) of endoscopic TSS was fewer postoperative nasoseptal perforations; the most commonly (34%) rated disadvantage was more postoperative complications, including cerebrospinal fluid leak. Respondents were divided on whether microscopic TSS should continue to be taught in residency. Many (32%) advocated for improved endoscopic instrumentation and team training. CONCLUSION: Endoscopic TSS is now the clearly preferred method for surgery amongst a cohort of higher-volume academic neurosurgeons. This trend is likely to continue, and this provides guidelines for future training.